2016
DOI: 10.1186/s12986-016-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of abscisic acid chronic treatment on neuroinflammatory markers and memory in a rat model of high-fat diet induced neuroinflammation

Abstract: BackgroundWestern diet and lifestyle are associated with overweight, obesity, and type 2 diabetes, which, in turn, are correlated with neuroinflammation processes. Exercise and a healthy diet are important in the prevention of these disorders. However, molecules inhibiting neuroinflammation might also be efficacious in the prevention and/or treatment of neurological disorders of inflammatory etiology. The abscisic acid (ABA) is a phytohormone involved in hydric-stress responses. This compound is not only found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 58 publications
3
39
2
Order By: Relevance
“…The activation of glial cells leads to the production of reactive oxygen and nitrogen species, initiation of phagocytosis, and upregulation of anti-proliferative and pro-inflammatory mediators. The levels of pro-inflammatory cytokines are reported to increase after starting HFD; among these, interleukin-1, interleukin-6, and tumor necrosis factor-α [41][42][43] are the most frequently reported. Increased chemokine expression (chemokine (C-X-C motif) ligand 1 and chemokine (C-C motif) ligand 3 (CCL3)) [39] and toll-like receptor-4 signaling pathway (inhibitor of nuclear factor κB -α (IκB-α) and nuclear factor κB) [44] have also been mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of glial cells leads to the production of reactive oxygen and nitrogen species, initiation of phagocytosis, and upregulation of anti-proliferative and pro-inflammatory mediators. The levels of pro-inflammatory cytokines are reported to increase after starting HFD; among these, interleukin-1, interleukin-6, and tumor necrosis factor-α [41][42][43] are the most frequently reported. Increased chemokine expression (chemokine (C-X-C motif) ligand 1 and chemokine (C-C motif) ligand 3 (CCL3)) [39] and toll-like receptor-4 signaling pathway (inhibitor of nuclear factor κB -α (IκB-α) and nuclear factor κB) [44] have also been mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Average fat oxidation in the MAP group was higher than in the SUC group, while CHO oxidation in the MAP group was lower. It has been reported that ABA including MAP has some influence on energy metabolism [12]. ABA administration reversed abnormal energy metabolism in obese humans and animals [12].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ABA including MAP has some influence on energy metabolism [12]. ABA administration reversed abnormal energy metabolism in obese humans and animals [12]. Likewise, thiazolidinedione (structurally similar to ABA) up-regulated the β-oxidation and free fatty acid transport-related genes in adipose cells [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at a central level, ABA administration in a mice model has demonstrated an anti-inflammatory protective effect, lowering microglia activation, decreasing TNFα levels, and restoring high-fat diet induced cognitive dysfunctions [49]. Recent studies also support an ABA role in modulating hippocampal neurogenesis [50].…”
Section: Aba Actions In Animalsmentioning
confidence: 99%